2016
DOI: 10.1111/jai.13025
|View full text |Cite
|
Sign up to set email alerts
|

Generalized additive models to predict adult and young brown trout (Salmo truttaLinnaeus, 1758)densities in Mediterranean rivers

Abstract: Wiley: 12 months Alcaraz-Hernández, JD.; Muñoz Mas, R.; Martinez-Capel, F.; Garófano-Gómez, V.; Vezza, P. (2016). Generalized additive models to predict adult and young brown trout (Salmo trutta Linnaeus, 1758) 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 88 publications
1
13
0
Order By: Relevance
“…Three major interrelated features requiring optimization control GAMs' performance: the number of selected inputs, overparameterization, which refers to the excessive number of effective degrees of freedom (Alcaraz‐Hernández, Muñoz‐Mas, Martínez‐Capel, Garófano‐Gómez, & Vezza, ), and data prevalence, which corresponds to the ratio of presence data within the entire dataset (Platts, McClean, Lovett, & Marchant, ). Therefore, a wrapper approach (see, e.g., Muñoz‐Mas, Fukuda, Vezza, & Martínez‐Capel, ), based on cross‐validation, genetic algorithm (GA), and evolutionary algorithm (Holland, ), was used to obtain the most relevant noncorrelated ( r 2 > 0·66; p ≤ 0·1) input variables (Peters et al, ), the optimal number of effective degrees of freedom (Arlot & Celisse, ), and the case weights, in order to balance the error committed on presence and absence data (Muñoz‐Mas, Lopez‐Nicolas, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Three major interrelated features requiring optimization control GAMs' performance: the number of selected inputs, overparameterization, which refers to the excessive number of effective degrees of freedom (Alcaraz‐Hernández, Muñoz‐Mas, Martínez‐Capel, Garófano‐Gómez, & Vezza, ), and data prevalence, which corresponds to the ratio of presence data within the entire dataset (Platts, McClean, Lovett, & Marchant, ). Therefore, a wrapper approach (see, e.g., Muñoz‐Mas, Fukuda, Vezza, & Martínez‐Capel, ), based on cross‐validation, genetic algorithm (GA), and evolutionary algorithm (Holland, ), was used to obtain the most relevant noncorrelated ( r 2 > 0·66; p ≤ 0·1) input variables (Peters et al, ), the optimal number of effective degrees of freedom (Arlot & Celisse, ), and the case weights, in order to balance the error committed on presence and absence data (Muñoz‐Mas, Lopez‐Nicolas, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Because microhabitat selection is typically a nonlinear process (e.g., Alcaraz-Hernandez, Munoz-Mas, Martinez-Capel, Garofano-Gomez, & Vezza, 2016;Girard et al, 2014;Labonne et al, 2003), we introduced B-splines to transform the microhabitat variables, which decomposed these variables into piecewise cubic regressions with fixed knots (Grajeda et al, 2016;Pan & Goldstein, 1998). For each model, we previously selected the appropriate number of knots between models with a single knot (fixed at 50% of the distribution of the microhabitat variable, two degrees of freedom) or models with two knots (fixed at 33 and 67% of the distribution of the microhabitat variable, three degrees of freedom).…”
Section: Modellingmentioning
confidence: 99%
“…() showed that elevation combined with local habitat features (e.g., cover) accounted for much of the variation of brown trout biomass and density across 264 stream reaches belonging to 15 streams. Local habitat attributes such as the mean velocity, the cover, the maximum depth, the distance between rapids, and the number of slow habitats were used together with the reach elevation to model young (<2 years) brown trout densities in the Júcar River Basin District (Spain; Alcaraz‐Hernández et al ., ). Depending on the local morphological and hydraulic characteristics, size‐class habitat selection patterns by brown trout exhibit large flexibility and adapt to local conditions (Ayllón, Almodóvar, Nicola, & Elvira, ), suggesting that the influence of a given habitat variable is site‐dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in space in trout population abundance, structure, or production are common, both within and among rivers (Milner, Gee, & Hemsworth, 1979;Milner, Wyatt, & Scott, 1993;Cattanéo et al, 2002;Lobón-Cerviá & Rincón, 2004;Almodóvar, Nicola, & Elvira, 2006;Lobón-Cerviá, 2007;Zorn & Nuhfer, 2007;Richard, Cattanéo, & Rubin, 2015). These dynamics can be related to catchment scale attributes (e.g., basin area, stream order, altitude, and geology) and climate, but much of this variability is explained by local scale attributes (i.e., site; e.g., depth, substrate site, cover, and water velocity, Milner, Hemsworth, & Jones, 1985;Armstrong, Kemp, Kennedy, Ladle, & Milner, 2003;Santiago et al, 2016;Alcaraz-Hernández, Muñoz-Mas, Martínez-Capel, Garófano-Gómez, & Vezza, 2016). In the French Pyrénées, Baran, Delacoste, Lascaux, and Belaud (1993); Baran, Delacoste, Poizat et al (1995) showed that elevation combined with local habitat features (e.g., cover) accounted for much of the variation of brown trout biomass and density across 264 stream reaches belonging to 15 streams.…”
mentioning
confidence: 99%